2017
DOI: 10.1016/j.euroneuro.2017.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Distinct lithium-induced gene expression effects in lymphoblastoid cell lines from patients with bipolar disorder

Abstract: Lithium is the most commonly prescribed medication for the treatment of bipolar disorder (BD), yet the mechanisms underlying its beneficial effects are still unclear. We aimed to compare the effects of lithium treatment in lymphoblastoid cell lines (LCLs) from BD patients and controls. LCLs were generated from sixty-two BD patients (based on DSM-IV) and seventeen healthy controls matched for age, sex, and ethnicity. Patients were recruited from outpatient clinics from February 2012 to October 2014. LCLs were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 68 publications
2
15
0
Order By: Relevance
“…Lymphoblastoid cell lines (LCLs) can be studied under controlled conditions, and have been used for functional studies that cannot be done with post-mortem brain tissue, such as identifying lithium induced gene expression changes in bipolar patients and controls (Fries et al, 2017). Recent studies have shown strong correlations between blood and brain for cis expression QTLs (eQTLs) and methylation QTLs (Qi et al, 2018).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Lymphoblastoid cell lines (LCLs) can be studied under controlled conditions, and have been used for functional studies that cannot be done with post-mortem brain tissue, such as identifying lithium induced gene expression changes in bipolar patients and controls (Fries et al, 2017). Recent studies have shown strong correlations between blood and brain for cis expression QTLs (eQTLs) and methylation QTLs (Qi et al, 2018).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…To relate our results to previous lithium findings, we compared the full set of DGE and DTE-only genes (n = 1108) with a set of genes associated with lithium in 18 previous transcriptomic reports [37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54] identified through a systematic literature search (Supplementary Materials and Methods). We found overlap with 112 genes (10.1%), many of them having similar direction and magnitude of effect (Table S3).…”
Section: Comparison Between Identified Genes and Previous Findingsmentioning
confidence: 99%
“…This activation is thought to occur, at least in part, through the phosphatidylinositol 3-kinase (PI3K) pathway, as Li exposure increases PI3K/Akt1 anti-apoptotic activity and inhibition of PI3K blocks the neurotrophic effects of Li. Our recent study evaluating Li-induced gene expression alterations in lymphoblastoid cell lines (LCL) from BD patients and controls supports a role for PI3K/Akt and anti-apoptotic pathways in Li mechanisms of action [1]. While treatment in LCLs from controls did not lead to any significant differences, Li altered the expression of 236 genes in cells from patients.…”
mentioning
confidence: 86%